EFEKTIVITAS KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN BUDAYA LITERASI DI MADRASAH ALIYAH AZIZIYYAH TANGERANG - El Khuluqo, Ihsana; Azizah, Alif Luthvi (Prosiding Seminar Nasional Berseri, 2020)
This research aimed at finding out the Effectiveness of School Principalâ€™s Leadership in Developing Culture of Literacy at Aziziyyah Islamic High School, Tangerang. The methods used was qualitative approach. The results of this study indicated that the design of literacy culture development in MA Aziziyyah Tangerang has been adapted to the GLS guidelines formulated by the Ministry of Education and Culture. Including the stages: Habituation Stages, Development Stages, and Learning Stages. Indicators of achievement in these stages were met with 30 items out of a total of 37 items. These results indicated that each stage in the design of literacy culture development ran optimally in accordance with the objectives to be achieved. Several factors influenced the development of literacy culture in MA Aziziyyah Tangerang, including: psychosocial factors, leadership factors, environmental factors, organizational factors, ecological factors, and government policies. These factors tended to have a positive impact on the process of developing literacy culture in MA Aziziyyah. The effectiveness of the principal’s leadership was the main foundation for optimizing the development of literacy culture. Indicators of achievement related to the effectiveness of MA Aziziyyah school principal leadership in developing a literacy culture fulfilled 6 items out of a total of 7 items. The results showed that the leadership carried out by the principal was quite effective.